Larval rearing of African carp, Labeo parvus Boulenger, 1902 (Pisces: Cyprinidae), using live food and artificial diet under controlled conditions. - MONTCHOWUI, HOUNNON ELIE; LALEYE, PHILIPPE A. (My University, 2011)
This study aimed at (1) evaluating the efficacy of live food organisms (Artemia and natural zooplankton) and an artificial diet in the larval rearing of African carp Labeo parvus and (2) determining appropriate rearing conditions. After yolk sac resorption, the larvae were separated into five different feeding trials with two replicates. At the end of the larval rearing period (28 days post-hatching), the highest (94.6%) and the lowest (53.7%) cumulative survival rates were found when larvae were fed with natural zooplankton for 7 days followed by Nippai food for 21 days, and when larvae were fed from the beginning of exogenous feeding with Nippai food only respectively. The significant highest body weight (351.6 mg), total length (34.4 mm) and specific growth rates (15.5%day _1) were recorded when the larvae were fed with Artemia nauplii for 14 days followed by Nippai food for 14 days. The lowest growth performance (body weight and specific growth rates) were obtained when larvae were fed exclusively Nippai food. These results indicate that L. parvus can be successfully cultured in indoor nursery systems from hatching to the early juvenile stage.
Keywords: Labeo parvus; larval rearing; nursery conditions; Cyprinidae